SISTEMATIKA IMPLEMENTASI INOVATIF TERHADAP PEMBELAJARAN PENDIDIKAN PANCASILA MAHASISWA - Risa Novita; Slamet Widodo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Pancasila education is a learning material that is implemented in the form of a theoretical explanation. Not a few students are bored and bored with the repetition of the theory conveyed since sitting in school until college. This is what makes the research objective to find out the systematic implementation of innovative implementation of Pancasila education for students, so that Pancasila education can internalize Pancasila values in students. This study uses a literature review method by collecting and analyzing data from sources of journal articles and the like. The result of this study is that there are problems when learning Pancasila education makes the learning competency not achieved. So there needs to be a systematic implementation of innovative implementation of Pancasila education learning. This will work well if there is a synergistic collaboration between the head dean, lecturers, students and residents in the campus environment. The head of the dean together with the lecturers collaborated to develop a teaching systematic and syllabus for learning Pancasila education. Then, the lecturer prepares a learning implementation plan with creative and innovative objectives, media, models, and learning methods. Therefore, students take part in learning comfortably and without boredom. Likewise, the campus environment also contributes to the internalization of Pancasila values as supporters and observers of students.